Determinants of greenhouse gas assurance provider choice. Issue 1 (10th April 2017) - Green, Wendy; Taylor, Stuart; Wu, Jennifer
Abstract : Purpose: This paper surveys corporate officers responsible for greenhouse gas (GHG) reporting and assurance to determine the attributes that influence their choice between an accounting and a non-accounting GHG assurance provider. Differences in the relative importance of these attributes between those selecting accounting and non-accounting assurers are also explored. Design/methodology/approach: A survey questionnaire was completed by 25 corporate officers responsible for reporting and voluntarily assurance of GHG emissions in Australia. The questionnaire asked the respondents to indicate the relative importance of 41 company and assurer attributes in influencing their assurance provider choice. Findings: Results indicate that attributes related to the assurance provider, such as team and team leader assurance knowledge, reputation, objectivity and independence, are more influential than attributes related to the nature of the company or the nature of the GHG emissions. Attributes such as geographical dispersion of operations were found to be differently important to this decision between companies purchasing assurance from accounting and non-accounting firms. Research limitations/implications: The study's main limitation is the small number of participants. Future research may extend this study by exploring the conditions under which companies voluntarily assure GHG emissions as well the motivations of responsible officers in their assurer choice. Practical implications: This paper provides valuable insights to GHG assurers to assist their understanding of the attributes that are important to potential GHG assurance clients. Originality/value: The study makes unique contributions to the assurer choice literature by not only addressing this issue in the context of the dichotomous GHG assurance market but also by addressing it from the perspective of the assurance purchaser.